Law in India : restructuring and reforming - Reddy, P. Jaganmohan (Jaipur, 1992)
This book contains a collection of 16 papers based on lectures delivered/ articles published by the author at the invitation of highly reputed organisations during the 1980s. They depict the various socio-economic and political problems faced by the Indian Society and its ongoing struggle to break the impasse created by them. The book discusses wide ranging issues such as the unity and secularism in India, functioning of the democratic institutions, efficacy of the present legal environment for correctional administration, problems encountered by the majority and 'minority' in the country, overhauling of the - caste system, Shabano Verdict, the right of private defence, sexual offences against women, bride burning, the freedom under law, ethics in medical profession, the need for instituting meritocracy and similarities and dissimilarities between the American and Indian Constitution. Justice Jaganmohan Reddy with his sharp insights into the functioning of the Indian society and deep involvement in Indian freedom movement has made an authoritative presentation of his views on the problems of natural importance.
Keywords: Law India